The genera Nothacrobeles Allen & Noffsinger, 1971 and Zeldia Thorne, 1937 (Nematoda: Rhabditida: Cephalobidae) from southern Iran, with description of N. abolafiai sp. n. - Mehdizadeh, Sara; Shokoohi, Ebrahim (Zootaxa, 2013)
A new species of the genus Nothacrobeles Allen & Noffsinger, 1971 is described from a natural area in Kerman Province, Iran. Nothacrobeles abolafiai sp. n. is characterized by its body length (518–655 μm in females), “single” cuticle, lateral field with three incisures, labial probolae 8.5–9.4 μm long, bifurcated and without tines, bearing a minor curvature at the tip, pharyngeal corpus 3.3–4.1 times isthmus length, Rex= 25–32, spermatheca 22–30 μm long or 0.8–1.2 times the corresponding body diameter, postuterine sac 15–18 μm long or 0.5–0.7 times the corresponding body diameter, female tail conical with rounded terminus (31–43 μm, c = 11.9–18.1, c' = 1.7–2.4), and phasmid at 38–43% of tail length. In addition, two species of the genus Zeldia Thorne, 1937: Z. punctata (Thorne, 1925) Thorne, 1937 and Z. spannata Waceke, Bumbarger, Mundo-Ocampo, Subbotin & Baldwin, 2005, were recovered. The latter is recorded for the first time from Iran. Description, measurements, illustrations and LM pictures are provided for these three species. Furthermore, comparative morphometrics for the species of Nothacrobeles are given. Molecular analysis based on 28S rDNA (D2-D3 expansion) places this new species of Nothacrobeles in a different clade to other Nothacrobeles species. The results suggest that the genus Nothacrobeles may be a paraphyletic taxon.